Analysis of Labor Productivity in Mechanical, Electrical, and Plumbing Works for a Multi-Story Building (Case Study: UPN "Veteran" East Java Twin Tower Building) - Natasya, Dininda; Putra, I Nyoman Dita Pahang (Jurnal Sains dan Teknologi (JSIT), 2024)
In a project construction , productivity power Work be one factor affecting efficiency and success project . This is very important in work Mechanical, Electrical and Plumbing (MEP) in buildings multilevel , where is precision time , quality , and reliability installation is very important comfort and security user building the . Study This aim for analyze productivity power working on Mechanical, Electrical and Plumbing (MEP) work on the construction of the UPN "Veteran" East Java Twin Tower Building. Collected data covers planning and realization in the site , such as coefficient power work , volume of work daily , total labor daily , and productivity power Work . The analytical method used is compare between productivity planning and productivity realization in the site . Research result show that there is difference significant productivity between planning and realization in the site . Actual productivity in the site is lower than planning productivity. These findings can be used as input for contractors to increase labor productivity on similar construction projects in the future.